Factors of anthropogenous impact on formation of the tourist environment of the Bakhchsarai area of Crimea - Borodich, Marina (Видавництво Львівської політехніки, 2013)
In article was revealed and processed culturalinformative and socio-economic factors of anthropogenous impact on formation of the tourist environment of the Bakhchsarai district.
Keywords: tourist environment; recreational complex; urban-planning system; anthropogenous factors